Single-crystal growth apparatus - Song Do Won; Kim Cheol Hwan; Choi Jun Hyuk; Lee Chang Youn; Son Jin Ho (2017)
Disclosed is a single-crystal growth apparatus including a chamber, a crucible provided in the chamber and configured to accommodate a melt that is a raw material for single-crystal growth, a heater disposed between the crucible and a side wall of the chamber and heating the crucible, and a crucible screen disposed on an upper end of the crucible, and the crucible screen has a bending member reflecting a radiant heat generated from the melt in the crucible to inside wall of the crucible.